Long term effect on IOP of a stainless steel glaucoma drainage implant (Ex-PRESS) in combined surgery with phacoemulsification. Issue 4 (17th March 2005) - Traverso, C E; De Feo, F; Messas-Kaplan, A; Denis, P; Levartovsky, S; Sellem, E; Badalà, F; Zagorski, Z; Bron, A; Belkin, M
Abstract : Aim: To evaluate the efficacy and safety of a stainless steel miniature glaucoma drainage device (Ex-PRESS R50) for the surgical treatment of primary open angle glaucoma (POAG) and cataract when combined with phacoemulsification. Methods: Clinical, prospective, multicentre, single treatment arm, non-randomised, non-masked study. The Ex-PRESS device was implanted at the limbus under a conjunctival flap. Phacoemulsification cataract extraction and in the bag IOL implantation were performed through clear cornea temporally. Primary outcome: IOP change; secondary outcomes: side effects and VA changes. Results: 26 eyes of 25 patients were implanted with the device. The mean (SD) follow up was 23.9 (10.4) months and the mean age was 75.1 (7.1) years. 17/26 eyes have more than 3 years of follow up. One case was discontinued because of device removal, one because of death, and three were lost to follow up. Efficacy: preoperative IOP was 21 (4) mm Hg; at 1, 2, and 3 years IOP was 15.3 (3.1) mm Hg (35% reduction), 16.6 (2.7) mm Hg (29% reduction), and 16 (2.6) mm Hg (22% reduction) respectively. Kaplan-Meyer determined overall success rate (IOP ⩽21 mm Hg at the last visit with or without medications) as 76.9%. The number of antiglaucoma medications was reduced by 95% at year 1. Only six patients (23%) were taking IOP lowering treatment at their last visit, five with one medication and one with two medications. Side effects: early postoperative complications were clinically mild and included six cases of hypotony (IOP <5 mm Hg), three cases of hyphaema (<2 mm) with no clinically significant further effects. Long term complications were two cases (7.7%) of device rotation (one treated by reposition) and three cases (11.5%) of conjunctival erosion at 2 and 3 years. Conclusions: The Ex-PRESS implant, combined with phacoemulsification cataract extraction, is clinically safe and effective, maintaining in the long term a large reduction in IOP and in the number of antiglaucoma medications.